2009
DOI: 10.1177/0960327109106548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thimerosal on Ca2+ movement and viability in human oral cancer cells

Abstract: The effect of thimerosal on cytosolic free Ca2+ concentrations ([Ca2+]i ) in human oral cancer cells (OC2) is unclear. This study explored whether thimerosal changed basal [Ca2+]i levels in suspended OC2 cells using fura-2. Thimerosal at concentrations between 1and 50 μM increased [Ca2+]i in a concentration-dependent manner. The Ca2+ si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(65 reference statements)
1
11
0
2
Order By: Relevance
“…It is an active low-molecular cyclitol isolated from the seed coat, cotyledon and embryo axis of soybean seeds (Kuo et al, 2009). Moreover, as a natural therapeutic agents it has gained much attention due to their diverse biological activities such as inhibition of the T-helpercell-1 response, antiviral, larvicidal, antiinflammatory, antihyperlipidemic, cardioprotective, inhibition of ovalbumin-induced airway inflammation and antioxidant (Sethi et al, 2008;Sivakumar et al, 2010).…”
Section: Thamaraiselvan Rengarajanmentioning
confidence: 99%
“…It is an active low-molecular cyclitol isolated from the seed coat, cotyledon and embryo axis of soybean seeds (Kuo et al, 2009). Moreover, as a natural therapeutic agents it has gained much attention due to their diverse biological activities such as inhibition of the T-helpercell-1 response, antiviral, larvicidal, antiinflammatory, antihyperlipidemic, cardioprotective, inhibition of ovalbumin-induced airway inflammation and antioxidant (Sethi et al, 2008;Sivakumar et al, 2010).…”
Section: Thamaraiselvan Rengarajanmentioning
confidence: 99%
“…There is also evidence of increasing intracellular Ca 2þ through thimerosal exposure in several non-kidney cell types (Pintado et al 1995;Chen, Harada, and Yamashita 1998;Kuo et al 2009). It is known that etHg is less neurotoxic than meHg in adult male and female rats (Magos 1986), but the potency of etHg/thimerosal in vitro to induce the cytotoxicity through rising intracellular levels of Ca 2þ on brain neurons from infant rats appears to be similar to that of meHg ).…”
Section: Intracellular Distribution Of Calciummentioning
confidence: 99%
“…By using different approaches, several groups demonstrated that both inorganic Hg and etHg/thimerosal induce apoptosis in several non-kidney cell lines (Guo et al 1998;Goering et al 1999;Baskin, Ngo, and Didenko 2003;Issa et al 2003;Humphrey et al 2005;Kuo et al 2009;Li et al 2012). Thimerosal was shown to induce DNA and membrane damage and also caspase-3-dependent apoptosis in the human neuronal and fibroblasts (Baskin, Ngo, and Didenko 2003), to activate caspase-9 and caspase-3 in T cells and human neuroblasts (Makani et al 2002;Humphrey et al 2005), and to activate the c-Jun N-terminal kinase pathway in neuroblastoma cells (Herdman et al 2006).…”
Section: Apoptosis and Necrosismentioning
confidence: 99%
“…Utilizando diferentes abordagens, vários grupos sugerem que o timerosal induz apoptose em diversas linhagens de células não-renais (BASKIN, et al, 2003;HUMPHREY, et al, 2005;KUO, et al, 2009;LI, et al, 2012). Até o momento, o único estudo que avaliou um potencial mecanismo de nefrotoxicidade do timerosal no tecido renal foi realizado por JAN e colaboradores que demonstraram que este agente organomercurial induz aumento de cálcio intracelular, em células renais caninas (Madin Darby canine kidney) (JAN, et al, 2003).…”
Section: Efeitos Citotóxicos Do Mercúrio No Tecido Renalunclassified
“…Diferentes estudos desenvolvidos em várias linhagens de células não-renais têm demonstrado que o timerosal induz apoptose (LI, et al, 2012;KUO, et al, 2009;HUMPHREY, et al, 2005;BASKIN, et al, 2003 -ACHANZAR, et al, 1996;GUO, et al, 1998;CARRANZA-ROSALES, et al, 2005;LEE, et al, 2006;TARABOVA, et al, 2006;SUTTON;TCHOUNWOU, 2007;KANDA, et al, 2008). No entanto, em relação a marcadores apoptóticos após exposição ao EtHg ou timerosal, no tecido renal não foram encontradas evidências na literatura.…”
Section: Timerosal Reduziu a Mitose E Promoveu Apoptoseunclassified